Christ Church garden, 1961 - Woodman, W.C. (Tufts Archival Research Center, 2005)
Street-level view of a garden at Christ Church, which is located on Salem Street at the southeast end of Hull Street. 4 3/8 x 6 3/8, 5 x 6 7/8 overall Photographs